Neoadjuvant sequential chemoradiotherapy versus radiotherapy alone for treatment of high-risk extremity soft tissue sarcoma: a single-institution experience - Kılıç, Leyla; Ekenel, Meltem; Karabulut, Senem; Ağaoğlu, Fulya; Darendeliler, Emin (Contemporary Oncology/Współczesna Onkologia, 2017)
Aim of the study : Patients with large and high-grade extremity soft-tissue sarcoma are at significant risk for distant metastasis and sarcoma-related death. There is no randomized trial comparing chemoradiotherapy to radiotherapy in the neoadjuvant setting for high risk extremity soft-tissue sarcoma. The aim of this study is to evaluate the outcomes of patients treated with two different modalities (neoadjuvant sequential chemoradiotherapy vs. radiotherapy alone) in a single center. Material and methods : Data of 67 patients were analyzed retrospectively. Thirty-four patients received neoadjuvant sequential chemoradiotherapy (2–3 cycles of doxorubicin (75 mg/m 2 ) and ifosfamide (6 g/m 2 ) followed by radiotherapy of 28 Grays (Gy) administered as 8 fractions of 35 Gy) and 33 patients received radiotherapy alone. R0 resection rates and 3-year survival estimates were evaluated. Results : Median follow-up time was 37 months. The estimated 3-year overall and disease-free survival rates for the whole patient group were 79% (95% CI: 67.0–86.4) and 57.9% (95% CI: 46.3–69.0), respectively. The most common side effects were nausea and leucopenia. Three-year overall, disease-free, local recurrence-free and distant recurrence-free survival rates did not differ significantly. All patients except one underwent wide excision or compartmental resection. R0 resection rate for the whole patient group was 92.5% (n = 62). Sites of progression were similar across both treatment arms. Conclusions : Preoperative hypofractionated radiotherapy alone or sequentially with chemotherapy result in high rates of limb salvage and acceptable toxicity. Our study results did not show a statistically significant treatment effect regarding survival and patterns of failure.